Synthesis and Characterization of Nanohydroxyapatite-Gelatin Composite with Streptomycin as Antituberculosis Injectable Bone Substitute - Hikmawati, Dyah; Maulida, Hendita N.; Putra, Alfian P.; Budiatin, Aniek S.; Syahrom, Ardiyansyah (International Journal of Biomaterials, 2019)
The most effective treatment for spinal tuberculosis was by eliminating the tuberculosis bacteria and replacing the infected bone with the bone graft to induce the healing process. This study aims to synthesize and characterize nanohydroxyapatite-gelatin-based injectable bone substitute (IBS) with addition of streptomycin. The IBS was synthesized by mixing nanohydroxyapatite and 20 w/v% gelatin with ratio of 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, and 75:25 ratio and streptomycin addition as antibiotic agent. The mixture was added by hydroxypropyl methylcellulose as suspending agent. FTIR test showed that there was a chemical reaction occurring in the mixture, between the gelatin and streptomycin. The result of injectability test showed that the highest injectability of the IBS sample was 98.64% with the setting time between 30 minutes and four hours after injection on the HA scaffold that represents the bone cavity and coat the pore scaffold. The cytotoxicity test result showed that the IBS samples were nontoxic towards BHK-21 fibroblast cells and human hepatocyte cells since the viability cell was more than 50% with significant difference (p-value<0.05). The acidity of the IBS was stable and it was sensitive towards Staphylococcus aureus with significantly difference (p-value<0.05). The streptomycin release test showed that the streptomycin could be released from the IBS-injected bone scaffold with release of 2.5% after 4 hours. All the results mentioned showed that IBS was suitable as a candidate to be used in spinal tuberculosis case.